Personalised transcranial magnetic stimulation for treatment-resistant depression, depression with comorbid anxiety and negative symptoms of schizophrenia: a narrative review - Xiao Wei Tan; Hasvinjit Kaur Gulwant Singh; Jovi Zheng Jie Koh; Rachel Si Yun Tan; Phern Chern Tor (Singapore Medical Journal)
Transcranial magnetic stimulation (TMS) is a promising intervention for treatment-resistant psychiatric disorders. However, conventional TMS typically utilises a one-size-fits-all approach when determining stimulation targets. Recent retrospective brain circuit-based analyses using lesion network mapping have suggested that a left dorsal lateral prefrontal cortex target has a higher efficacy for alleviating depression symptoms, a dorsomedial prefrontal cortex target is more effective for anxiety symptoms, and a rostromedial prefrontal cortex target is effective for schizophrenia-associated psychiatric symptoms. Nonetheless, symptom-specific brain circuit targeting has not been tested prospectively. We conducted a narrative review of selected literature to investigate individualised targeting for TMS and discuss potential future directions to elucidate the efficacy of this approach.